A pooled analysis of randomized, controlled, phase 3 trials investigating the efficacy and safety of a novel, fixed dose calcipotriene and betamethasone dipropionate cream for the topical treatment of plaque psoriasis. (5th November 2021) - Pinter, A.; Green, L.J.; Selmer, J.; Praestegaard, M.; Gold, L.S.; Augustin, M.; ,
Abstract: Background: Plaque psoriasis is a common, chronic and relapsing inflammatory skin disease clinically characterized by erythema and scaling desquamation. As over 90% of psoriasis patients benefit from topical therapies, local treatments continue to play an eminent role in management strategies. One such topical treatment is the fixed dose combination of calcipotriol (CAL) and betamethasone dipropionate (BDP). Objectives: Pooled analysis of two different phase 3 clinical trails to compare superiority regarding efficacy, safety and quality of life (QoL) between CAL/BDP PAD‐cream and CAL/BDP TS. Methods: The data from two phase 3, multicentre, randomized, investigator‐blind, active and vehicle‐controlled trials enrolling patients with psoriasis were pooled and analysed. Investigational products included a CAL/BDP cream based on PAD™ Technology (PAD‐cream) designed for high skin penetration and increased patient preference, an active control (marketed CAL/BDP topical suspension/gel, in the following abbreviated as CAL/BDP TS) and cream vehicle, which were applied once daily for 8 weeks. Results: Efficacy and safety of the novel CAL/BDP PAD‐cream formulation for the topical treatment of psoriasis demonstrated superiority for all efficacy end points after 8 weeks of treatment. PGA treatment success for CAL/BDP PAD‐cream (43.2%) was greater than CAL/BDP TS (31.9%; P < 0.0001), the mean per cent reduction in mPASI for CAL/BDP PAD‐cream was 64.6% compared to 56.4% for CAL/BDP TS ( P < 0.0001) and DLQI 0/1 was obtained by 43.8% in the CAL/BDP PAD‐cream group versus 34.2% in the CAL/BDP TS group ( P = 0.0005). There was no adverse drug reaction reported with a frequency of >1%, associated with the CAL/BDP PAD‐cream. Conclusions: The novel fixed dose combination CAL/BDP PAD‐cream offers greater efficacy, superior patient QoL and equivalent favourable safety for the topical treatment of psoriasis, in comparison to the currently available topical suspension/gel.